2020
DOI: 10.1155/2020/8185037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Limited Proteolysis by Trypsin on the Formation of Soy Protein Isolate Nanofibrils

Abstract: Nanofibril system constructed by protein self-assembly is widely used in the food industry because of purposive functional properties. Soy protein isolate nanofibrils (SPINs) were reported to form via heating at pH 2.0. In this research, the soy protein isolate (SPI) hydrolysate prepared by trypsin was used as a raw material for the formation of nanofibrils called soy protein isolate hydrolysate nanofibrils (SPIHNs). Microscopic images demonstrated the formation of two nanofibrils. Based on circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…With respect to the morphology of nanofibrils, SPI tended to form long and semiflexible nanofibrils, while the β‐conglycinin hydrolysates tended to produce short and worm‐like nanofibrils when both SPI and β‐conglycinin hydrolysates were heated at pH 2.0 and 90°C for 60 min, respectively (Xia et al., 2017). Based on these viewpoints, we used the SPI hydrolysates obtained by trypsin to fabricate nanofibrils at pH 2.0 and 85°C and determined the properties of the resulting nanofibrils (An & Li, 2020). We also found that nanofibrils maintained the integrity of α‐helix structures, whereas hydrolysates obtained by papain and neutral protease did not form nanofibrils.…”
Section: Processing Methods Controlling Food‐grade Protein Fibrillationmentioning
confidence: 99%
“…With respect to the morphology of nanofibrils, SPI tended to form long and semiflexible nanofibrils, while the β‐conglycinin hydrolysates tended to produce short and worm‐like nanofibrils when both SPI and β‐conglycinin hydrolysates were heated at pH 2.0 and 90°C for 60 min, respectively (Xia et al., 2017). Based on these viewpoints, we used the SPI hydrolysates obtained by trypsin to fabricate nanofibrils at pH 2.0 and 85°C and determined the properties of the resulting nanofibrils (An & Li, 2020). We also found that nanofibrils maintained the integrity of α‐helix structures, whereas hydrolysates obtained by papain and neutral protease did not form nanofibrils.…”
Section: Processing Methods Controlling Food‐grade Protein Fibrillationmentioning
confidence: 99%
“…This initial change in the native monomer might even be brought about by chemicals (not necessarily denaturants). For example, proteolysis of a short stretch of polypeptide or glycosylation, changes brought about by pH might alter the aggregation propensity of the protein molecules [192][193][194]. The conformational and/or chemical changes in the native monomer might even be brought about by physical cues, such as pressure, etc.…”
Section: Mechanism-2: Aggregation Of Conformationally/chemically Modi...mentioning
confidence: 99%
“…These findings suggest that fibrillation processes of ꞵ-conglycinin and glycinin were different and could be mutually affected when these two components coexist in SPI. Apart from our study, only one study so far explored the effects of enzymatic proteolysis on the formation of soy protein fibrils [223]. In that study, the authors used traditional proteolysis and mentioned that the hydrolysate prepared by papain were less favorable for the formation of nanofibrils, but neither microscope images nor the enzymatic conditions were provided [223].…”
Section: Selective Proteolysismentioning
confidence: 98%
“…Apart from our study, only one study so far explored the effects of enzymatic proteolysis on the formation of soy protein fibrils [223]. In that study, the authors used traditional proteolysis and mentioned that the hydrolysate prepared by papain were less favorable for the formation of nanofibrils, but neither microscope images nor the enzymatic conditions were provided [223]. In here, the ability of DβH to form longer and semiflexible fibrils could make it a promising thickening agent or structural ingredients, as these protein fibrils proved to have high viscosity and shear thinning behavior [6].…”
Section: Selective Proteolysismentioning
confidence: 99%